Monocyte‐derived extracellular vesicles stimulate cytokine secretion and gene expression of matrix metalloproteinases by mesenchymal stem/stromal cells. (18th May 2018) - Gebraad, Arjen; Kornilov, Roman; Kaur, Sippy; Miettinen, Susanna; Haimi, Suvi; Peltoniemi, Hilkka; Mannerström, Bettina; Seppänen‐Kaijansinkko, Riitta
Abstract : Intercellular communication is essential in bone remodelling to ensure that new bone is formed with only temporary bone loss. Monocytes (MCs) and osteoclasts actively take part in controlling bone remodelling by providing signals that promote osteogenic differentiation of mesenchymal stem/stromal cells (MSCs). Extracellular vesicles (EVs) have attracted attention as regulators of bone remodelling. EVs facilitate intercellular communication by transferring a complex cargo of biologically active molecules to target cells. In the present study, we evaluated the potency of EVs from MCs and osteoclasts to induce a lineage‐specific response in MSCs. We analysed gene expression and protein secretion by both adipose tissue‐derived MSCs and bone marrow‐derived MSCs after stimulation with EVs from lipopolysaccharide‐activated primary human MCs and (mineral‐resorbing) osteoclasts. Isolated EVs were enriched in exosomes (EVs of endosomal origin) and were free of cell debris. MC‐ and osteoclast‐derived EVs were taken up by adipose tissue‐derived MSCs. EVs from activated MCs promoted the secretion of cytokines by MSCs, which may represent an immunomodulatory mechanism. MC‐derived EVs also upregulated the expression of genes encoding for matrix metalloproteinases. Therefore, we hypothesize that MCs facilitate tissue remodelling through EV‐mediated signalling. We did not observe a significant effect of osteoclast‐derived EVs on gene expression or protein secretion in MSCs. EV‐mediated signalling might represent an additional mode of cell‐cell signalling during the transition from injury and inflammation to bone regeneration and play an important role in the coupling between bone resorption and bone formation. Database: Gene expression data are available in the GEO database under the accession numberGSE102401 . Abstract : We analysed gene expression and protein secretion by mesenchymal stem/stromal cells (MSCs) after stimulation with extracellular vesicles (EVs) derived from lipopolysaccharide‐activated primary human monocytes and (mineral‐resorbing) osteoclasts. Monocyte‐derived EVs stimulated cytokine secretion and upregulated the expression of matrix metalloproteinase expression by MSCs. Osteoclast‐derived EVs on the other hand, did not affect MSC gene expression significantly.